Cubo de Rubik com ênfase no ambiente escolar - Santos, Daniel Marcus dos (2021)
The present work has as object of study the Rubik's cube (or magic cube) with emphasis on the benefits brought by its use in the school environment, thus exploring the use for teaching some mathematics subjects in Elementary School. In this work a brief history of the Rubik's Cube will be presented, as it emerged and became one of the most famous puzzles in the world. In order to provide support to students in solving the Rubik's cube, some videos were also made available with one of the methods for solving the magic cube, the “layer method”. The methods used in this research were bibliographic research, with a qualitative approach, of an exploratory type, in which information was sought in books, articles, dissertations, theses and on the Web, among others. We also use field research. However, the COVID-19 pandemic greatly affected field research. We base our work on the ideas of Gervázio (2017, p. 44 apud MICOTTI, 1999), Moya (2015) and Dijoli (2017).